Prognostic Role of Programmed Death Ligand-1 on Tumor-Infiltrating Immune Cells in “High-Risk” Patients Following Radical Cystectomy: A Retrospective Cohort Study - Lee, Chung Un; Lee, Dong Hyeon; Song, Wan (Frontiers in Oncology, 2021)
Purpose: The aim of this study is to investigate the prognostic role of programmed death ligand-1 (PD-L1) on tumor-infiltrating immune cells (TIICs) in patients after radical cystectomy (RC) for bladder cancer (BCa). Materials and Methods: We retrospectively reviewed 92 “high-risk” (≥pT3a and/or pN+) patients who underwent RC for BCa, without adjuvant chemotherapy (AC), between April 2014 and December 2019. PD-L1 on TIICs was measured only using the VENTANA (SP-142) immunohistochemistry assay. Patients were categorized into three groups based to the percentage of the tumor area covered by PD-L1 on TIICs: IC0 (<1%), IC1 (≥1% and <5%), and IC2/3 (≥5%). Positive PD-L1 was defined as IC2/3 (≥5%). Kaplan–Meier survival analysis was used to illustrate recurrence-free survival (RFS), and Cox proportional hazard models were used to identify predictive factors of tumor recurrence. Results: Within the cohort, the proportions of PD-L1 IC0, IC1, and IC2/3 were 21.7%, 23.9%, and 54.4%, respectively. At follow-up (mean 31.3 months), tumor recurrence was identified in 49 patients (53.3%). Using multivariable analysis, tumor stage (pT4; P=0.005), positive lymph nodes (P=0.021), and positive PD-L1 on TIICs (P=0.010) were independent predictors of tumor recurrence. The 2- and 3-year RFS rates were 67.7% and 64.2% in negative PD-L1 on TIICs, while 27.8% and 22.3% in positive PD-L1 on TIICs, respectively. Conclusions: Positive PD-L1 on TIICs was significantly associated with poorer RFS in “high-risk” patients after RC without AC. Our results support the use of adjuvant immunotherapy in “high-risk” patients with positive PD-L1 on TIICs after RC.